Anthecological features of Lonicera japonica Thunb. in the environments of Southern Uzbekistan - Kh. K. Djumayev; K. G. Tkachenko (Труды по прикладной ботанике, генетике и селекции)
Background. Identification of spectacular ornamental perennial lianas for urban landscaping in southern cities is important for modern urban greening programs. The aim of this work was to study flowering peculiarities of Japanese honeysuckle (Lonicera japonica Thunb.).Materials and methods. The target material was honeysuckle plants growing in the environments of Southern Uzbekistan. Observations were conducted in 2019–2020 using conventional approaches.Results and conclusion. The inflorescence of L. japonica is an open dibotryoid, with flowers arranged along the lateral axes of the first order. Flowers are bisexual, zygomorphic. Blossoming of flowers in inflorescences occurs acropetally. The flowering period is almost 150–170 days (starts in April and lasts until the end of August). Dichogamy in the form of proterandry is observed in honeysuckle flowers. The male flowering phase comes the first. It starts 1.5–2.0 hours after the opening of the corolla and ends with the drying of the stamens. The corolla turns yellow 36 hours after the blooming of the flower and the stamens begin to dry out. This is the female phase. Over the next 84 hours, the pistil begins to dry out slowly, but the corolla of the flower lasts up to 96 hours. The duration of the female flowering phase is 60 hours. L. japonica is of considerable interest for vertical landscaping of urban communities. Plants remain ornamental for a long time. Studying this species as an essential oil plant is promising, since it contains a significant amount of germacrene D.